Pembentukan Kepribadian Berbasis Uluhiyyah: Kajian Ontologis Terhadap Metode Pendidikan Salaf - Robbaniyyah, Khodijah Irbatur; Addawiyah, Aishah Ayu; Alfiyah, Nur; Gustiranda, Anugrah; Noorhayati, Siti Mahmudah (Interdisciplinary Explorations in Research Journal, 2026)
Islamic education plays a strategic role in developing a resilient human personality oriented toward its purpose as a servant of Allah. However, modern Islamic education faces a personality crisis characterized by moral degradation, spiritual disorientation, and value fragmentation a consequence of the dominance of pedagogical-instrumental approaches and the neglect of the ontological dimension of Tawhid. Most studies in Islamic education overlook Uluhiyyah as the ontological foundation of personality formation, focusing instead on methodological and psycho-sociological aspects. This study aims to examine the concept of Uluhiyyah as the ontological basis of the Islamic personality and to analyze how the educational methods practiced by the Salafus Shalih contribute to the formation of an Uluhiyyah based personality. This research employs a qualitative approach through library research, analyzing relevant classical and contemporary literature via conceptual and ontological lenses. The results indicate that Uluhiyyah serves as the center of existential consciousness that integrates human reason, heart, and action, forming a consistent, stable personality oriented toward servitude to Allah. It is evident that the educational methods of the Salaf, which emphasize the purification of Tawhid, exemplary character (uswah), habitual worship, the cultivation of adab, and tazkiyatun nafs, can fully manifest the Islamic personality. This study suggests that revitalizing Uluhiyyah-based education is an urgent necessity for reconstructing the paradigm of modern Islamic education. Consequently, this paradigm will be capable of addressing the character and spiritual crises prevalent in the modern era.